Dipeptidyl peptidase-4 (DPP-4) inhibition with linagliptin reduces western diet-induced myocardial TRAF3IP2 expression, inflammation and fibrosis in female mice - Aroor, Annayya R. (Cardiovasc Diabetol, 2017)
BACKGROUND: Diastolic dysfunction (DD), a hallmark of obesity and primary defect in heart failure with preserved ejection fraction, is a predictor of future cardiovascular events. We previously reported that linagliptin, a dipeptidyl peptidase-4 inhibitor, improved DD in Zucker Obese rats, a genetic model of obesity and hypertension. Here we investigated the cardioprotective effects of linagliptin on development of DD in western diet (WD)-fed mice, a clinically relevant model of overnutrition and activation of the renin-angiotensin-aldosterone system. METHODS: Female C56Bl/6 J mice were fed an obesogenic WD high in fat and simple sugars, and supplemented or not with linagliptin for 16 weeks. RESULTS: WD induced oxidative stress, inflammation, upregulation of Angiotensin II type 1 receptor and mineralocorticoid receptor (MR) expression, interstitial fibrosis, ultrastructural abnormalities and DD. Linagliptin inhibited cardiac DPP-4 activity and prevented molecular impairments and associated functional and structural abnormalities. Further, WD upregulated the expression of TRAF3IP2, a cytoplasmic adapter molecule and a regulator of multiple inflammatory mediators. Linagliptin inhibited its expression, activation of its downstream signaling intermediates NF-κB, AP-1 and p38-MAPK, and induction of multiple inflammatory mediators and growth factors that are known to contribute to development and progression of hypertrophy, fibrosis and contractile dysfunction. Linagliptin also inhibited WD-induced collagens I and III expression. Supporting these in vivo observations, linagliptin inhibited aldosterone-mediated MR-dependent oxidative stress, upregulation of TRAF3IP2, proinflammatory cytokine, and growth factor expression, and collagen induction in cultured primary cardiac fibroblasts. More importantly, linagliptin inhibited aldosterone-induced fibroblast activation and migration. CONCLUSIONS: Together, these in vivo and in vitro results suggest that inhibition of DPP-4 activity by linagliptin reverses WD-induced DD, possibly by targeting TRAF3IP2 expression and its downstream inflammatory signaling.